TGFβ1 neutralization displays therapeutic efficacy through both an immunomodulatory and a non-immune tumor-intrinsic mechanism - Canè, S; Van Snick, J; Uyttenhove, C; Pilotte, L; Van den Eynde, BJ (BMJ Publishing Group, 2021)
Background Transforming growth factor-β (TGFβ) is emerging as a promising target for cancer therapy, given its ability to promote progression of advanced tumors and to suppress anti-tumor immune responses. However, TGFβ also plays multiple roles in normal tissues, particularly during organogenesis, raising toxicity concerns about TGFβ blockade. Dose-limiting cardiovascular toxicity was observed, possibly due to the blockade of all three TGFβ isoforms. The dominant isoform in tumors is TGFβ1, while TGFβ2 and TGFβ3 seem to be more involved in cardiovascular development. Recent data indicated that selective targeting of TGFβ1 promoted the efficacy of checkpoint inhibitor anti-PD1 in transplanted preclinical tumor models, without cardiovascular toxicity.